Islas Flotantes Artificiales con la Especie Achira (canna indica) como alternativa para la Remocion de Cromo y Coliformes Fecales en Agua Procedente del Rio Cutuchi - Aguiar Terán, María Belén (2019)
Artificial Floating Islands are systems of phytoremediation of polluted waters, comparable to natural wetlands. The goal of this research lays in the evaluation of the Achira species (C. Indica) as a potential agent for water treatment of Cutuchi river through the removal of Cr and fecal coliforms. As to it, an artificial floating island with an area of 0.09 m² was installed in a water-body of 115 liters (Treatment 1), three repetitions and a witness. The evaluation of the removed parameters was performed every 1 and 3 weeks, a process that was developed along 4 months. The results achieved in removal percentages were: chromium 98.88 % and fecal coliforms 89.68 %, representative values that prove the efficiency of systems with C. Indica varieties, establishing it as a natural alternative to improve the water quality of Cutuchi River.